A study of Activity-Based Learning Focusing on Multiple Intelligences that Affected Math and Language Abilities of Early Childhood Learners - นุชนารถ ลัดดาวัลย์; คงเรือง สุภัทรา; จุ้นดอนกลอย วริสรา (Journal of Educational Review Faculty of Education in MCU, 2018)
A study of activity-based learning focusing on multiple intelligences that affected math and language abilities of early childhood learners. A sample group was acquired through a multi-stage sampling. It consisted of 50 early childhood learners aged 3-4 from ๒ centers. A draw was conducted. The first group, the experiment group, consisted of 25 learners from Wat Chatthong (Luang Prachanukul) School. The group learned from the activity-based teaching focusing on multiple intelligences. Another group, the control group, consisted of 25 learners from Rungwitthaya (Pracha Uppatham) School. The group learned from the experience corner designed based on the teacher’s manual of the Local Administrative Development Department. The experiment period covered 4 weeks, 5 days with a total of 20 times. Research instruments consisted of 1) plans of learning at a multiple intelligences center and plans of learning by following the teacher’s manual of the Local Administrative Development Department; 2) math test and the language test. Quasi-experimental research was employed. Pre and post experimental tests were conducted. Statistics used to analyze the data was Multivariate of Analysis of Variance (MANOVA).